ЭФФЕКТИВНОСТЬ РЕГУЛЯТОРОВ РОСТА ПРИ ПРИМЕНЕНИИ МЕТОДОВ БИОТЕХНОЛОГИИ В СЕМЕНОВОДСТВЕ КАРТОФЕЛЯ (Experimental biology, 2015)
It is shown that the productively of potato greatly increases using the preparation sodium humate.
Keywords: sodium humate; potato greatly